The Effect of Net Profit Margin and Earning Per Share on Share Prices - Abiyu Sa’ad Ramadhan; Ayke Nuraliati (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
The net profit margin is a financial ratio in measuring a company's ability to generate a return on sales. Earning per share is a financial ratio that shows the profit from each outstanding share. The share price is the price of the company's shares listed and can change every second. The purpose of this study is to determine the influence of net profit margin on stock prices and to determine the magnitude of the influence of earnings per share on stock prices. This research was conducted at Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. The results in this study found that: 1) The t value of the net profit margin of 5.378 is greater than the t table of 2.00665 and the significant value of 0.000 is less than 0.05, it can be concluded that the net profit margin has a significant effect on stock prices; 2) It is obtained that the t value of earning per share is 3.349 which is greater than the t table of 2.00665 and a significant value of 0.002 is less than 0.05, so it can be concluded that earning per share has a significant effect on stock prices.